The Varieties of Scientific Experience: A Personal View of the Search for God - Carl Sagan (Penguin Press, 2006)
Sagan sets down his detailed thoughts on the relationship between religion and science and describes his personal search to understand the nature of the sacred in the vastness of the cosmos. In 1985, Sagan was invited to give the famous Gifford Lectures in Scotland on the grand occasion of the lectureship's centennial. The result is this delightfully intimate discussion of his views on topics ranging from the likelihood of intelligent life on other planets to the danger of nuclear annihilation of our own, on creationism and so-called intelligent design to a new concept of science as "informed worship" to manic depression and the possible chemical nature of transcendence. In his trademark clear and down-to-earth voice, the late astronomer and astrophysicist illuminates his conversation with examples from cosmology, physics, philosophy, literature, psychology, cultural anthropology, mythology, theology, and more.--From publisher description.